Ferromagnetic resonance study of iron implanted PET foils - OKAY, CENGİZ (WILEY-V C H VERLAG GMBH, 2006)
Polyethylene terephthalate (PET) foils were implanted with 40 keV Fe+ ions to doses of (0.15-1.50) x 10(17) ions/cm(2) at ion current density of 4 mu A/cm(2). The iron-implanted PET composites were investigated using ferromagnetic resonance (FMR) technique supplemented by transmission electron microscopy (TEM), atomic force microscopy (AFM) and DC resistance measurements. TEM studies revealed formation of iron nanoparticles with size in the range of 5-100 run depending on the implantation dose. AFM images showed depending on the implantation dose either small bumps or worm-like structures on the polymer surface that corresponded to the inclusions towered above the surface. The results of AFM studies were found to be in good agreement with the TEM measurements. FMR signal was observed for the foils implanted with the dose higher than 0.15 x 10(17) ions/cm(2). The effective magnetization of the metal-polymer composite was extracted from the angular dependencies of FMR resonance field. The percolation transition at the implantation dose of 1.0 x 10(17) ions/cm(2) was observed in the dose dependencies of the FMR absorption intensity and the effective magnetisation. The minimum in DC resistance found at the same dose indicates that a charge carrier mediated (exchange) interaction rather than the dipolar one is underlying mechanism for the percolation transition. Formation of a carbonized layer in the heavily implanted area of the polymer is supposed to be responsible for the exchange coupling of the magnetic granules. (c) 2006 WILEY-VCH Verlag GmbH & Co. KGa.A, Weinheim.
Keywords: THIN-FILMS